ChemInform Abstract: Diastereoselective Synthesis of Dibenzoazepines Through Chelation on Palladium(IV) Intermediates. Issue 26 (1st July 2014) - Narbonne, Vanessa; Retailleau, Pascal; Maestri, Giovanni; Malacria, Max
Abstract A palladium/norbornene catalyst provides access to dibenzo[c, e]azepines.